Evolution of Pediatric Inflammatory Bowel Disease Unclassified (IBD-U): Incorporated With Serological and Gene Expression Profiles. Issue 10 (30th May 2018) - Chandradevan, Raguraj; Hofmekler, Tatyana; Mondal, Kajari; Harun, Nusrat; Venkateswaran, Suresh; Somineni, Hari K; Ballengee, Cortney R; Kim, Mi-Ok; Griffiths, Anne; Noe, Joshua D; Crandall, Wallace V; Snapper, Scott; et al.
Abstract: Background: Inflammatory bowel disease (IBD) mainly consists of Crohn's disease (CD) and ulcerative colitis (UC). About 10%–15% of patients with IBD cannot be firmly diagnosed with CD or UC; hence, they are initially diagnosed as inflammatory bowel disease unclassified (IBD-U). Having a firm diagnosis is clearly preferred to guide treatment choices, and better understanding of the nature of IBD-U is required. Methods: We performed an analysis of a subset of pediatric subjects from an inception IBD cohort of patients initially enrolled in a prospective multicenter study (the RISK study). Initial diagnosis and 2-year follow-up data from the subjects diagnosed with IBD-U were analyzed. An expert panel verified final diagnosis using predefined criteria as a guide. Serological and disease-relevant ileal and rectal tissue gene expression profiles were investigated. The use and the time to initiate anti-TNFα treatment was analyzed among the outcome groups. Results: A total of 1411 subjects were enrolled with initial diagnosis of IBD, and among them, 136 subjects were initially diagnosed as IBD-U at enrollment. And 26% were reclassified as UC and 14% as CD within 2 years of diagnosis, while 60% remained as IBD-U. Of those who were reclassified, there was a 2:1 ratio, UC (n = 35) to CD (n = 19). The molecular and serological features of IBD-U at the end of follow-up were very similar to UC and very different from CD. There was less likelihood of receiving anti-TNFα agents if the diagnosis was IBD-U compared with CD ( P < 0.0001). Conclusions: In our cohort, 60% of the IBD-U subjects remained as unclassified at 2 years; of those subsequently classified, a higher percentage followed a course more similar to UC. Most of the IBD-U subjects at diagnosis had serological and molecular signatures that are very similar to UC. Although the atypical presentations made the clinician to make an interim diagnosis of IBD-U, results of the molecular and serological factors performed at the time of diagnosis suggests that they were very similar to UC. However, long-term studies are needed to better understand the natural history and molecular characterization of pediatric onset IBD-U.